Synthesis of Mixed Ligand Complexes of M(II) Dithiocarbamato Derivative and 2,2'-bipyridyl and Study their Cytotoxic Effect Against HepG2 Cell Line in vitro - Baghdad Science Journal (مجلة بغداد للعلوم, 2015)
Mixed ligand of Co and Ni (II) complexes were prepared from [5-(p-nitrophenyl)-4/-phenyl-1,2,4-triazole-3-dithiocarbamato hydrazide](TRZ.DTC) as primary ligand and 2,2'-bipyridyl (bipy) as a co-ligand with metal salts. These complexes were analytically and spectroscopically characterized in solid state by elemental analyses, flame atomic absorption, magnetic susceptibility and molar conductance measurements, as well as by UV–Vis and FTIR spectroscopy. Infrared, ultra violet spectra reveal a bidentate coordination of the two ligands with metal ions 1:1:1 mole ratio. Room temperature magnetic moments and solid reflectance spectra data indicate paramagnetic complexes with five-coordinate square pyramidal geometry for nickel (II) complex, while six-coordinate octahedral geometry for cobalt (II) complex in solid state. The mixed ligand and its respective complexes were screened for cytotoxicity assay on human HepG2 cell line using cis-Pt drug as a control positive following the cell culture method for 3 days after treatment with the tested compounds using eight different concentrations. The bioassay results showed good inhibition activity of these synthetic compounds especially Ni (II) complex on selected cell lines comparable with standard drug.